Act on the Measures and Actions During the State of Emergency and on Addressing the Consequences - A Means to Overcome or Deepen the Negative Economic Consequences of the COVID-19 Pandemic? - Aleksandrov, Andrey (Research Papers, 2021)
In the past years the labor relations have faced a number of economic, political, and now – the so far unknown “epidemical” crises. To overcome their negative consequences, various legal mechanisms have been sought, which should have given some experience to the legislator to respond in a crisis situation. It is therefore least disturbing that the wrong legislative concept (or rather lack thereof) has led to a number of changes in our labor law since the state of emergency was declared on 13 March 2020. The study aims to outline at least some of the problems of this legal uncertainty, in the hope of preventing the recurrence of such mistakes in the future.